The Effects of Sundanese Kacapi Suling “Ayun Ambing” Music Therapy to The Level of Anxiety on Chronic Renal Failure Patient Undergoing Hemodialysis - Mustopa Saepul Alamsah; Laili Rahayuwati; Chandra Isabella Hostanida Purba (Jurnal Keperawatan Padjadjaran, 2018)
ABSTRACT One of the most common psychological problems found in patients with chronic renal failure (ESRD) undergoing hemodialysis is anxiety. Unresolved anxiety can have a negative impact on physiological and psychological conditions that can aggravate the condition of the disease. Traditional Sundanese music therapy Kacapi Suling "Ayun Ambing" has a slow tempo and soft so that it can be used as a therapy. The purpose of this study was to determine the effect of the music therapy Sunda Kacapi Suling "Ayun Ambing" to the anxiety level of patients undergoing hemodialysis.The design used was a Quasy Experimental, with a pretest-posttest control group design approach, involved 46 patients divided into control groups (23) and intervention groups (23) taken by purposive sampling. The intervention group get given Sundanese Kacapi Suling "Ayun Ambing" of music a week 2 times with time 30 minutes for 2 weeks. Anxiety levels were measured using HARS (Hamilton Anxiety Rating Scale) before and after intervention. The control group received standard interventions provided by the Hospital. Data were analyzed univariate and bivariate with Paired t test, Independent t test and Mann Whitney test.Characteristics of respondents between the intervention group and the homogeneous control did not differ significantly. Differences of average before and after in two groups with the tested paired t test showed no significant difference with p value <0.05 whereas for differences in the average change of scores between the intervention and control group with independent t test showed there was a significant difference with p value 0.05.In conclusion, Sundanese Kacapi Suling "Ayun Ambing" of music intervention has an influence on the anxiety with patient undergoing hemodialysis. An implication of this research was that Sundanese Kacapi Suling Music could be considered and applied as a complementary theraphy to decrease the anxety of client, particularly ESRD undergoing hemodialysis. Sundanese Kacapi Suling "Ayun Ambing" of music intervention can also be used as an intervention alternative in a further research in order to overcome health therapies such as anxiety and pain. Keywords: Chronic Kidney Failure, Hemodialysis, Anxiety, Music Kacapi Suling